2020
DOI: 10.1177/1010428320909999
|View full text |Cite
|
Sign up to set email alerts
|

Samarium enriches antitumor activity of ZnO nanoparticles via downregulation of CXCR4 receptor and cytochrome P450

Abstract: Cancer is the leading cause of death and exhausts human and economic resources for treatment and protection. Zinc oxide nanoparticles play an effective role in tumor treatment but with some cautions, such as overexpression of cytochrome P450, hepatic overload, and the mammalian target of rapamycin pathway resistance. Although lanthanides have antitumor activity, their use is limited. Therefore, the current study aims to improve the effectiveness of zinc oxide nanoparticle via doping with lanthanides, such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Sm is also proved to enhance anticancer activity in combination with ZnO. Sm 3+ ion-doped ZnO showed dose-dependent antiproliferative activity on cancerous cells. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sm is also proved to enhance anticancer activity in combination with ZnO. Sm 3+ ion-doped ZnO showed dose-dependent antiproliferative activity on cancerous cells. , …”
Section: Resultsmentioning
confidence: 99%
“…Sm 3+ ion-doped ZnO showed dose-dependent antiproliferative activity on cancerous cells. 8,36 Research studies were performed to understand the anticancer activity of lanthanides. In osteosarcoma, the cytochrome P-450 governs the tumor microenvironment and tumorigenesis.…”
Section: Immersion Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, have also shown that the biological activity of samarium doped hydroxyapatite (SmHAp) it is strongly influenced by the amount of Sm 3+ that is found in the samples [10][11][12][13][14]. Moreover, has been highlighted that the presence of Sm 3+ in various biomaterials, used in the medical field, increases their anticancer activity [15,16]. Ying L. and collaborators, in their study entitled "Long-term biodistribution in vivo and toxicity of radioactive/magnetic hydroxyapatite nanorods", showed that Sm-HA:Gd nanorods exhibit an excellent γ-emission, relaxivity and biocompatibility thus making them suitable for potential applications in the biomedical area (including single-photon emission computed tomography (SPECT) and magnetic resonance imaging (MRI) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of nanoparticles and coatings in the medical field is on an upward trend due to their remarkable properties that make them effective in many ways, starting from the fight against pathogenic microorganisms and ending with their antitumoral activity [1]. One of the most used biomaterials in the biomedical field is hydroxyapatite (HAp, Ca 10 (PO 4 ) 6 (OH) 2 ) which is the main mineral component of bone tissue.…”
Section: Introductionmentioning
confidence: 99%